PERAN GREENPEACE DALAM MENANGANI KERUSAKAN LINGKUNGAN DI SEKTOR INDUSTRI FAST FASHION - Putri, Nabila Endina; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this study was to find out how Greenpeace's role in the second hand September campaign was to deal with environmental damage in the fast fashion industry sector. Fast fashion can be defined as trendy clothing models that are produced quickly to match the constantly changing fashion concepts. Fast fashion is made with a faster process, uses low-quality raw materials, and is sold at low prices. So that fashion can be bought by everyone from various circles.            The type of research used by the author is qualitative research with analytical descriptive data processing using library data collection techniques, namely utilizing secondary data obtained through literature studies which are abstracted from various literatures such as books, journals, bulletins, newspapers, annual reports of several agencies related documents, or other materials. Fast fashion industry waste can contaminate human habitation and cause diseases that have an impact on health quality.             The negative impact is also felt by the fast fashion industry workers. Therefore, international organizations such as Greenpeace participate in dealing with environmental damage caused by fast fashion. Another factor that can affect the success of the campaign is also because of the public's view of NGOs which are considered as one of the actors who always act correctly when compared to other actors. Keywords: Fast Fashion, Environmental Damage, Greenpeace, Second Hand                      September Campaign